2023
DOI: 10.1186/s41043-023-00391-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between screen use and central obesity among children and adolescents: a systematic review and meta-analysis

Mohammad Ghasemirad,
Leyla Ketabi,
Ehsan Fayyazishishavan
et al.

Abstract: Currently, there is no summative study evaluating the association between central obesity and screen time. This systematic review and meta-analysis aimed to summarize the results of studies evaluating the association between screen time and central obesity among children and adolescents. To this end, we performed a systematic search in three electronic databases, including Scopus, PubMed, and Embase to retrieve the related studies up to March 2021. Nine studies were eligible to be included in the meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This has been linked to advanced technology. A systematic review and meta-analysis by Ross et al (51) reported playing video games and spending too much time watching television is associated with central obesity in children (51)(52)(53). Dietary patterns have also been identified as a significant risk factor for central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to advanced technology. A systematic review and meta-analysis by Ross et al (51) reported playing video games and spending too much time watching television is associated with central obesity in children (51)(52)(53). Dietary patterns have also been identified as a significant risk factor for central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The body weight status of each participant was categorized as follows: normal weight (BMI ≥ 5th percentile and < 85th percentile), overweight (BMI ≥ 85th percentile and < 95th percentile), and obesity (BMI ≥ 95th percentile) [1]. Central obesity was indicated as WC value is ≥ 85th percentile according to international age, sex and height specific cut-offs of WC [21].…”
Section: Outcome Measuresmentioning
confidence: 99%